(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The reservation policy for Scheduled Castes is generally important, since it is connected with their social and economic character. Reservation is the privilege of the SC and STs, in any case, there have been high pace of disparity in the implementation of reservation policy in India. Be that as it may, in the current setting, the Scheduled Castes have accomplished a good level of education all over India. The disparity in the implementation of reservation policy for SCs has come about into serious economic consequences, which are firmly associated with their life. Even following 59 years of Independence, the reservation status of SCs in all Government branches has been unsuitable. The reservation policy has been underutilized. An Inspite of Constitutional provision, the reservation policy has been neglected. The plans for socio-economic upliftment of sterilization laborersforagers and their reliant’s should be promoted.